FAMILY COMMUNICATION PATTERN RELATION WITH DEPRESSIONLEVEL ON ELDERLY IN POSYANDU ELDERLY - Triwibowo, Heri (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2025)
Elderly age said to be the final stage of development in the life cycle. In this period a person experiencing a physical setback,mental social gradually decreasing ability to adapt to changes and environmental stress often cause psychosocial disorders in elderly. One of which is depression. To cope with depression in the elderly required functional family communication because of the confidence will increase and the motivation to face problems that ocur will increase. Independent variable that is Family Communication Pattern and Dependent Variable is Depression Level. The research design uses analytical design on cross sectional design. Sample amounted to 30 respondents.With Purposive Sampling.The questionnaires used were two kinds of family communication pattern questionnaire and GDS (Geriatric Depression Scale). .The Stabilistic Test used is the Lambda Correlation test. The result of p (0,032) and α (0,05), so that p (0,032) <α (0,05) meaning that H0 is rejected and H1 accepted which means there is relation of family communication pattern with depression level in elderly at posyandu ugly village Jaringansari Hamlet Karangdiyeng Village .Dysfunctional family communication patterns can cause elderly sad, lonely and experiencing a lot of pressure consequently elderly will experience psychosocial problems especially depression. Functional family communication shows the existence of support to the family and increase the motivation to solve the problem, especially depression experienced by the elderly.